Birt–Hogg–Dubé syndrome: Clinical and molecular aspects of recently identified kidney cancer syndrome. (25th November 2015) - Hasumi, Hisashi; Baba, Masaya; Hasumi, Yukiko; Furuya, Mitsuko; Yao, Masahiro
Abstract: Birt–Hogg–Dubé syndrome is an autosomal dominantly inherited disease that predisposes patients to develop fibrofolliculoma, lung cysts and bilateral multifocal renal tumors, histologically hybrid oncocytic/chromophobe tumors, chromophobe renal cell carcinoma, oncocytoma, papillary renal cell carcinoma and clear cell renal cell carcinoma. The predominant forms of Birt–Hogg–Dubé syndrome‐associated renal tumors, hybrid oncocytic/chromophobe tumors and chromophobe renal cell carcinoma are typically less aggressive, and a therapeutic principle for these tumors is a surgical removal with nephron‐sparing. The timing of surgery is the most critical element for postoperative renal function, which is one of the important prognostic factors for Birt–Hogg–Dubé syndrome patients. The folliculin gene ( FLCN ) that is responsible for Birt–Hogg–Dubé syndrome was isolated as a novel tumor suppressor for kidney cancer. Recent studies using murine models for FLCN, a protein encoded by the FLCN gene, and its two binding partners, folliculin‐interacting protein 1 (FNIP1) and folliculin‐interacting protein 2 (FNIP2), have uncovered important roles for FLCN, FNIP1 and FNIP2 in cell metabolism, which include AMP‐activated protein kinase‐mediated energy sensing, Ppargc1a‐driven mitochondrial oxidative phosphorylation and mTORC1‐dependent cell proliferation. Birt–Hogg–Dubé syndrome is a hereditary hamartoma syndrome, which is triggered by metabolic alterations under a functional loss of FLCN/FNIP1/FNIP2 complex, a critical regulator of kidney cell proliferation rate; a mechanistic insight into the FLCN/FNIP1/FNIP2 pathway could provide us a basis for developing new therapeutics for kidney cancer.